Investigation of electronic and vibrational properties of dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate under high-pressure conditions. Issue 12 (24th March 2021) - Fan, Junyu; Su, Yan; Zhao, Jijun
Abstract : The vibrational and electronic properties of TKX-50 reveal the enhanced intermolecular hydrogen bonds cause the change of intramolecular geometry of TKX-50, thereby triggering possible structural transformation. Abstract : Dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate (TKX-50), a newly found ionic energetic material with excellent performance and low sensitivity, has attracted much attention. In this work, the high-pressure response of vibrational properties in conjunction with structural and electronic properties are investigated to understand its stability under hydrostatic and uniaxial compressions. From our calculations, the band gap of TKX-50 broadens up to 0.5 GPa, then gradually shrinks at 0.5–10 GPa due to the unusual evolution of the a -axis. Analysis of the Mulliken population implies that the pressure dependence of the band gap is weak due to the inhibition of charge transfer under hydrostatic pressure. The Raman spectra of TKX-50 under uniaxial and hydrostatic compressions were simulated. The results suggest that TKX-50 undergoes multiple possible structural transformations under uniaxial compressions through discontinuous modifications of bond lengths in the cation moieties, whereas it maintain structural stability up to 10 GPa under hydrostatic conditions. Overall, the investigation of the electronic properties and uniaxial compression responses increases knowledge of TKX-50 under high-pressure conditions.